Justification and critique towards a critical theory of politics - Forst, Rainer; Cronin, Ciaran (Cambridge, [England] Polity Press, 2014)
Rainer Forst develops a critical theory capable of deciphering the deficits and potentials inherent in contemporary political reality. This calls for a perspective which is immanent to social and political practices and at the same time transcends them. Forst regards society as a whole as an "order of justification" comprising complexes of different norms referring to institutions and corresponding practices of justification. The task of a "critique of relations of justification", therefore, is to analyse such legitimations with regard to their validity and genesis and to explore the social and political asymmetries leading to inequalities in the "justification power" which enables persons or groups to contest given justifications and to create new ones. -- Publisher description.
Introduction : On the Idea of a Critique of Relations of Justification -- Part I Radical Justice -- Two Pictures of Justice -- The Justification of Human Rights and the Basic Right to Justification : A Reflexive Approach -- The Normative Order of Justice and Peace -- Part II Justification, Recognition, and Critique -- The Ground of Critique : On the Concept of Human Dignity in Social Orders of Justification -- First Things First : Redistribution, Recognition, and Emancipation -- Part III Beyond Justice -- The Injustice of Justice : Normative Dialectics According to Ibsen, Cavell, and Adorno -- The Republicanism of Fear and of Redemption : On the Topicality of Hannah Arendt's Political Theory -- Utopia and Irony : On the Normativity of a Political Philosophy of "Nowhere."
Originally published as Kritik der Rechtfertigungsverhältnisse : Perspektiven einer kritischen Theorie der Politik by Suhrkamp Verlag : Berlin, 2011.
Translated from the German language.
Keywords: Political science -- Philosophy; Justice